Factors affecting the adoption of mobile services. Issue 1 (12th December 2008) - Kargin, Banu; Basoglu, Nuri; Daim, Tugrul
Mobile technologies are gaining more popularity and diffusing into different aspects of our life. Value added services (VAS) have a huge impact on consumers' usage patterns and have become a significant differentiator across the operators, which has led to new opportunities in the innovation of differentiating and useful services. This paper explores the process of mobile service adoption and targets identifying the preferred features of mobile services. A series of interviews were conducted to address the objectives listed. A model was developed based on the factors identified. The major aspects of the model are service and social.